2016
DOI: 10.1007/s11187-016-9713-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting new venture survival and growth: Does the fog lift?

Abstract: This paper investigates whether new venture performance becomes easier to predict as the venture ages: does the fog lift? To address this question we primarily draw upon a theoretical framework, initially formulated in a managerial context by Levinthal (Adm Sci Q 36(3):397-420, 1991) that sees new venture sales as a random walk but survival being determined by the stock of available resources (proxied by size). We derive theoretical predictions that are tested with a 10-year cohort of 6579 UK new ventures in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…Growth, as discussed above, is therefore assumed to be random, and only after time passes and resource accumulation is realised does it become easier to predict survival (Coad et al, 2016). In this study we are able to hypothesise that those entrepreneurs with a greater general growth motivation will be more likely to survive, as they are more likely to have sufficient accumulated resources to withstand negative competitive and macroeconomic shocks.…”
Section: Growth Motivationmentioning
confidence: 85%
See 2 more Smart Citations
“…Growth, as discussed above, is therefore assumed to be random, and only after time passes and resource accumulation is realised does it become easier to predict survival (Coad et al, 2016). In this study we are able to hypothesise that those entrepreneurs with a greater general growth motivation will be more likely to survive, as they are more likely to have sufficient accumulated resources to withstand negative competitive and macroeconomic shocks.…”
Section: Growth Motivationmentioning
confidence: 85%
“…However, this does tend to imply that the entrepreneurs themselves have no control over their fates. One particular course of action that could have profound implications for survival is the capability to grow and accumulate sufficient resources to withstand external shocks (Caliendo, Fossen, and Kritikos 2010;Coad et al 2013;Coad et al, 2016). However, a counter argument to this thesis is provided by Delmar, McKelvie, and Wennberg (2013) who find a negative relationship between growth in one period and survival in the next in the case of knowledge intensive start-ups, which they suggest may relate to growth itself being a risky activity.…”
Section: Growth Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, as shown in other empirical studies (Haltiwanger et al, 2016;Hurst and Pugsley, 2011;Stam and Wennberg, 2009), firms located around the central percentiles of the distribution experience negligible employment growth. In other words, a substantial share of new firms experiences negative or no growth whereas expansion in employment is, by no means, a common feature of new firms dynamics (Coad et al, 2016b). However, a small fraction of new firms exhibits very high rates of employment growth.…”
Section: Dependent Variablementioning
confidence: 99%
“…This is important given that start-ups in services in the US and most other advanced economies surmount manufacturing start-ups roughly 8 to 1 (Kim et al, 2006). Third, a further advantage granted by employing a sample of firms established in the same year is that it allows the examination of businesses facing the same macroeconomic conditions during their development and can, therefore, be meaningfully compared (Anyadike-Danes et al, 2015;Coad et al, 2016b;Ryder, 1965). This is especially important since recent literature has shown that macroeconomic conditions have significant effects on both firm characteristics and performance at their entry and during subsequent years (Gomis and Khatiwada, 2017;Lee and Mukoyama, 2015).…”
Section: Datamentioning
confidence: 99%